Prestasi Kerja Pegawai Di Dinas Perhubungan Kota Medan Berdasarkan Kebutuhan Penghargaan dan Kebutuhan Sosial - Muhammad Wahyu Hidayat; Abd. Rasyid Syamsuri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to analyze the influence of esteem needs and social needs on employee work performance in the Medan City Transportation Department. The population of this study was 301 employees of the Medan City Transportation Department. The sample in this study was 172 employees of the Medan City Transportation Department. The analytical methods used are Validity Test and Reliability Test, Classical Assumption Test, Multiple Regression Analysis, T Test, F Test and Coefficient of Determination. The research results partially prove that the need for appreciation has a positive and significant effect on employee work performance at the Medan City Transportation Service. Social needs have a positive and significant influence on the Medan City Transportation Department. Simultaneously, the research results show that the need for esteem and social needs have a positive and significant effect on the Medan City Transportation Department. The R square (R2) value shows that the coefficient of determination is 0.534, meaning that the percentage of Reward Needs (X1) and Social Needs (X2) on Job Performance is 53.4% while the rest is influenced by other variables that were not studied. Keywords: Reward Needs, Social Needs, Work Achievement